Performance Analysis of CloudLinux-based Web Server at the Embassy of the Kingdom of Morocco in Jakarta - Anggie Pratama Lalengke; Ida Nurhaida (ISB Atma Luhur, 2021)
The rapid development of Information Technology (IT) has made a high availability web server a necessity. CloudLinux is a CentOS-based operating system specifically for the needs of servers with good high availability. This study will implement and analyze a CloudLinux-based web server for the Embassy of the Kingdom of Morocco in Jakarta to replace the current CentOS-based web server that does not meet high availability standards. The research methodology used in this study is the PPDIOO Life-cycle from Cisco. Designing a network according to the customer's needs requires identifying several elements in it, including the goals and constraints faced by the organization. Cisco creates a network life-cycle that can help these problems into six phases: Prepare, Plan, Design, Implement, Operate, and Optimize (PPDIOO). This study aims to determine how well the uptime, response time, and load impact are on the CloudLinux-based web server. The uptime test results on the CloudLinux-based web server have a value of an average of 99.971%. Testing the response time on the CloudLinux-based web server has an average value of 684.75ms (milliseconds). The results of the load impact test on the CloudLinux-based web server using ten virtual users (10VU) has a total value of 7595 requests, load impact using fifteen virtual users (15VU) has a total value of 11315 requests, and finally, load impact using twenty-five virtual users (25VU) has a total value of 18631 requests.